Controlling asthma and related allergies - alternative options - Haq, Ehtishamul; Banday, Mujeeb Zaffar (Journal of Research in Biology, 2012)
Asthma is a medical condition that causes narrowing of small airways in the lungs. Asthma is a chronic inflammation of lung passages, involving eosinophils, mast cells, T-cells, neutrophils, macrophages. Typically, asthma patients develop wheezing and have increased mucous production in their lungs, which causes breathlessness and chest tightness particularly during night. The most common inhaled allergens that trigger asthma attacks are: pollen, cockroach allergens, animal dander, mites in house dust, fungi (molds) that grow indoors, chemicals, fumes, or airborne industrial pollutants, smoke. In addition, inflammation in asthma can also be triggered by: viral respiratory infections, gastrooesophageal reflux disease & other conditions. In the year 2007 report by WHO estimates that more than 300 million people suffer from asthma worldwide, and almost 2,50,000 deaths attributed to the disease. In the past decade much of interest has been shown in alternative medicine and asthma was not an exception. The authors have summed up the alternative treatment strategies, which may atleast be used as adjunct in the treatment of asthma and related allergies.